PEMUTUSAN RANTAI PENULARAN CORONAVIRUS DISEASE (COVID-19) MELALUI PEMANFAATAN TANAMAN OBAT KELUARGA (TOGA) PADA IBU HAMIL, NIFAS, MENYUSUI DAN LANSIA - Enny Fitriahadi; Yekti Satriyandari (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
The pandemic period requires people to always be vigilant and adhere to health protocols. The period in which a woman from pregnancy, childbirth, postpartum, breastfeeding to the elderly is a continuous process. In the process, they experience various discomforts such as fatigue, vaginal discharge, cravings, frequent urination, emesis gravidarum, dizziness, aches and many other complaints. Early detection of complications of pregnancy, childbirth, postpartum, breastfeeding and the elderly can be assessed through integrated service standards that are usually carried out at posyandu and health centers. During the current pandemic, people are still afraid to go to the nearest health facility for examination and treatment. For this reason, it is health workers who provide solutions or alternative health service activities through cadres or community leaders. The next problem is the increasing number of Covid-19 cases in Sleman Regency which will have an impact on women's health, which is still quite worrying and the lack of knowledge of mothers regarding the prevention of COVID-19 in the family and surrounding areas. The service team from Aisyiyah University Yogyakarta helped PRA Aisyiyah Nogotirto and the community together to break the chain of transmission of COVID-19 through the consumption of rhizomes. Based on the results of the pre and post tests regarding knowledge of covid-19 prevention in the family and community, PRA Nogotirto mothers understand and are able to implement healthy living and always maintain health protocols in the family and community environment.